A scientometric analysis of research progress and trends in the design of laccase biocatalysts for the decolorization of synthetic dyes. (March 2023) - Rodrigues, Antonio F.S.; da Silva, Ananias F.; da Silva, Francisco L.B.; dos Santos, Kaiany M.; de Oliveira, Marcelo P.; Nobre, Millena M.R.; Catumba, Batista D.; Sales, Misael B.; Silva, Allison R.M.; Braz, Ana Kátia S.; Cavalcante, Antonio L.G.; Alexandre, Jeferson Y.N.H.; et al.
Abstract: This article conducted an advanced and comprehensive scientometric analysis of worldwide trends in decolorizing synthetic dyes by laccase. Articles were collected, analyzed, and classified according to the different substrates, enzymes, supports, immobilization procedures, and reactors involved. These studies were carried out in 200 institutions across 58 countries, with only 10 concentrating 88% of the total publications. China, India, and Turkey were identified as the main contributors to this research theme. Additionally, 26% of the institutions surveyed published only one article in the analyzed period. The results of the presented analysis encompassed data generated from 1999 to 2021, spanning more than two decades of specialized research. A ranking of article publications in scientific journals involving laccase, immobilization, enzymes, and dyes is listed. Also listed are the ranking of the 10 most prolific countries in the area of immobilized enzymes and the 10 most cited articles on the immobilization of enzymes with dyes. This analysis includes information related to the methods of support and costs of manufacture involving enzyme and immobilization routes. Finally, a discussion is presented exploring the fact that innovative technologies have been developed to render enzyme production more sustainable and economically viable. Highlights: Laccase for the decolorization of dyes is assessed via the bibliometric method. China, India, and Turkey are the main contributors to the decolorization of dyes via laccase. Support and manufacturing costs involving laccase immobilization routes are presented. Biotechnology and Applied Microbiology were the most common research topic. A growing application of laccase in the commercial area was observed.